Kajian Ketersediaan Air di DAS Sampean Baru Untuk Irigasi Perkebunan Pisang Cavendish (Musa Acuminata L) PT. XYZ di Kabupaten Bondowoso (Water Availability Study in The Sampean Baru Watershed for Irrigation of Cavendish Banana (Musa Acuminata L) Plantations at PT. XYZ in Bondowoso Regency) - Elida Novita; Idah Andriyani; Heru Ernanda; Halimatus Silvia; Hendra Andiananta Pradana (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
Cavendish bananas, which are popular internationally, could boost Indonesian horticultural exports. PT. XYZ specializes in the cultivation of Cavendish bananas, has a banana plantation in Bondowoso Regency's Sampean Baru Watershed. Factors that must be considered to ensure that the cultivation process runs smoothly include the availability of sufficient water to support cultivation activities. This study aimed to determine the condition of the Sampean Baru Watershed water balance due to the existence of Cavendish banana plantations owned by PT. XYZ. This study involves calculating water availability using FJ. Mock model and calculating water needs, which include calculating the water needs of PT. XYZ's Cavendish banana plantation, agricultural water needs, domestic-non-domestic water needs, and livestock water needs in the Sampean Baru Watershed area. The data used include climatology data, rainfall data, plant data, watershed area data, Bondowoso Regency planting plan data, land cover maps, and soil type maps. The results show that the Sampean Baru Watershed can meet the current water needs of banana plantations and for development purposes. The water balance condition is in surplus in all months. The total water requirement for PT. XYZ's Cavendish banana plantation is currently 0.00976 m3/s. The total surplus generated is 301.86 m3/s, with the total water requirement for agriculture, domestic, non-domestic, and livestock being 44.189 m3/s. Development can be carried out until the Cavendish banana plantation is 13,230.24 ha in area, because the water balance is balanced under these conditions. It is recommended that development not exceed this value to anticipate a deficit condition.